Pharmacodynamics of romiplostim alone and in combination with pegfilgrastim on acute radiation-induced thrombocytopenia and neutropenia in non-human primates. (2nd January 2020) - Wong, Karen; Chang, Polly Y.; Fielden, Mark; Downey, Anne Marie; Bunin, Deborah; Bakke, James; Gahagen, Janet; Iyer, Lalitha; Doshi, Sameer; Wierzbicki, Wieslaw; Authier, Simon
Abstract: Purpose: Evaluation of the pharmacodynamics (PD) and pharmacokinetics (PK) of romiplostim alone and in combination with pegfilgrastim in a non-human primate (NHP) model of acute radiation syndrome (ARS). Materials and methods: Male and female rhesus macaques were subjected to Cobalt-60 γ irradiation, at a dose of 550 cGy 24 h prior to subcutaneous administration of either romiplostim alone as a single (2.5 or 5.0 mg/kg on Day 1) or repeat dose (5.0 mg/kg on Days 1 and 8), pegfilgrastim alone as a repeat dose (0.3 µ g/kg on Day 1 and 8), or a combination of both agents (romiplostim 5.0 mg/kg on Day 1; pegfilgrastim 0.3 µ g/kg on Days 1 and 8). Clinical outcome, hematological parameters and PK were assessed throughout the 45 d study period post-irradiation. Results: Administration of romiplostim, pegfilgrastim or the combination of both resulted in significant improvements in hematological parameters, notably prevention of severe thrombocytopenia, compared with irradiated, vehicle control-treated NHPs. The largest hematologic benefit was observed when romiplostim and pegfilgrastim were administered as a combination therapy with much greater effects on both platelet and neutrophil recovery following irradiation compared to single agents alone. Conclusions: These results indicate that romiplostim alone or in combination with pegfilgrastim is effective at improving hematological parameters in an NHP model of ARS. This study supports further study of romiplostim as a medical countermeasure to improve primary hemostasis and survival in ARS.